2016
DOI: 10.5223/pghn.2016.19.2.110
|View full text |Cite
|
Sign up to set email alerts
|

The Association betweenHelicobacter pyloriInfection and Body Weight among Children

Abstract: PurposeWe performed to reveal the association between the Helicobacter pylori infection and body weight among children.MethodsOut retrospective study included patients who underwent the H. pylori immunoglobulin G testing at Konyang University Hospital between March 2011 and June 2014. These patients were classified as seropositive (28 boys, 27 girls; mean age: 9.89±3.28 years) or seronegative (55 boys, 54 girls; mean age: 9.84±3.02 years). Next, we compared various characteristics between the seropositive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(43 reference statements)
2
13
1
Order By: Relevance
“…While H. pylori was associated in several studies, no relationship was found between H. pylori and increased BMI (Ioannou et al, 2005;Marcela et al, 2007;Arslan et al, 2009). On the other hands, several studies showed an increase in BMI after H. pylori eradication (Ioannou et al, 2005;Choi et al, 2016). In our study, no relationship was found between BML levels and H. pylori positivity.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…While H. pylori was associated in several studies, no relationship was found between H. pylori and increased BMI (Ioannou et al, 2005;Marcela et al, 2007;Arslan et al, 2009). On the other hands, several studies showed an increase in BMI after H. pylori eradication (Ioannou et al, 2005;Choi et al, 2016). In our study, no relationship was found between BML levels and H. pylori positivity.…”
Section: Discussioncontrasting
confidence: 52%
“…The role of breastfeeding is controversial. Results of some studies found breastfeeding as a risk factor due to intimate contact between the infant and its infected mother (Malaty et al, 1996;Dore et al, 2002;Fialho et al, 2010;Choi et al, 2016). No study has been conducted in Duhok city determining H. pylori infection associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…30 A retrospective study reported that children administered H. pylori eradication therapy exhibited a significant weight gain compared to untreated children. 31 Thus, future studies are required to investigate whether early H. pylori eradication is necessary to prevent H. pylori-associated diseases including GC and their transmission to descendants. 32 The European and North American Societies for Pediatric Gastroenterology, Hepatology, and Nutrition recommend the use of triple therapy including proton-pump inhibitors (PPIs) in combination with amoxicillin and either imidazole or clarithromycin as a first-line treatment method for H. pylori eradication therapy in children.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is a common infection having a role in the development of different gastric lesions (Carabotti et al 2014). Several studies have stated that infection of H. pylori is associated with various extragastric conditions, such as diabetes mellitus (DM), dyslipidemia, and cardiovascular disease (Quatrini et al 2001;Choi et al 2016).…”
mentioning
confidence: 99%